Synthesis and characterization of carbon-based nanostructured material electrodes for designing novel hybrid supercapacitors - Manyala, Ncholu I. (University of Pretoria, 2018)
Recent research efforts are focused on alternative energy production instead of fossil fuels. Meanwhile, the developments of more efficient energy storage devices are driven by many factors. One is related to our environment. There is a need to significantly control emission of greenhouse gases, and reduce the amount of global warming majorly caused by fossil fuels. The products of combustion processes from fossil fuel usually lead to environmental pollution and poisonous atmospheric smog in our environment. In spite of growing developments in addressing various issues inherent to energy storage devices, supercapacitors continue to exhibit low energy density when compared with lithium ion batteries. The study in this thesis has utilized low-cost and environmentally-friendly carbon-based nanostructured hybrid materials as electrodes for designing a novel hybrid supercapacitor, which allows for a bolstering alliance of characteristics of dissimilar components in synergistic combinations, therefore providing enhanced energy and power densities by combining battery and supercapacitor materials storage mechanisms. Morphologies, compositions, structures and surface area/pore size distribution of the as-prepared materials nanocomposites were characterized using field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDX), X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, thermal gravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller (BET) and X-ray fluorescence (XRF), while the performance characteristics were electrochemically evaluated through cyclic voltammetry and charge/discharge cycling in both three- and two-electrode configurations. Electrodes fabricated from both graphene oxide (GO) nanogel gel and carbon nanorods materials gave a maximum specific capacitance of 436.5 F g-1 and 719.5 F g-1 corresponding to specific capacities of 48.5 mAh g-1 and 80.8 mAh g-1 at a specific current of 0.5 A g-1 respectively. The assembled hybrid asymmetric supercapacitor with carbonized iron cations (C-FP) selected as the negative electrode, NiCo-MnO2//C-FP proved a specific capacitance of 130.67 F g-1, high energy and power densities of 48.83 Wh kg-1 and 896.88 W kg-1 at 1 A g-1 respectively, with an excellent cycling stability for up to 10,000 cycles. Also, an assembled Ti3C2-Mn3O4//C-FP delivered a specific capacity of 78.9 mAh g-1, high energy and power densities of 28.3 Wh kg-1 and 463.4 W kg-1 at 1 A g-1 respectively. The device showed good cycling stability with an energy efficiency of 90.2% and capacitance retention of 92.6% for up to 10,000 cycles at a specific current of 3 A g-1 over a voltage window of 1.5 V. It is can be observed that electrolyte selection is critically important to achieving better performance for carbon-based material electrodes for enhanced supercapacitors electrochemical performance. Thus, this work is subjected to further studies by exploiting organic and ionic liquid electrolytes that may greatly enhanced the energy density and stability of the device.